Cyber Literature as an Alternative for Sidoarjo Woman Writers Community: A Sociological Perspective in Literature - Niko Fediyanto; Vidya Mandarani; Yuli Astutik (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2021)
The development of the globalization information system and the effects of the global pandemic almost demands almost everyone to optimize technology in response to various problems, including literature and writing. This article presents cyber literature as an alternative for the development of Pena Perajut Aksara, a women writers community in Sidoarjo. The problems studied were how the pattern of writing strategies for this community and how the community responds to cyber literature development as an alternative writing strategy. To answer the problems raised, researchers used a qualitative descriptive method. Theoretically, the researcher applied Pierre Bourdieu's perspective on the Field of Cultural Production. The data collected by using the unstructured interview method. The results of this study indicate that as the main strategy, this community relies on the curation of authors who have been consecrated as curators. Meanwhile, the development of electronic/cyber-literature has also begun to be taken seriously as a strategy to achieve consecration for this community. As an impact of research limitations on descriptive patterns, this study's results suggest more comprehensive and multi-disciplinary research to provide more concrete and measurable recommendations for the community in achieving consecration and broader public recognition in the future.